The Study of Morals According to Alawi bin Abdul Qadir Ash-Saqâf in the Book of Mausû’ah al-Akhlâq Volume Four - Nur Khowin, Ari Jalu; Basuki, Basuki; Saputro, Eko (Jurnal Penelitian Pendidikan Islam, 2024)
The object of this research is an examination of the dichotomy of morals according to Alawi bin Abdul Qadir Ash-Saqâf. This is important to research because it is related to a person’s moral degradation, so it needs to be discussed further. This research uses library research by utilizing primary and secondary data sources. The primary data source is the book Mausû‘ah al-Akhlâq volume 4, while the secondary data source is articles related to morals. The technique used to explore data is documentation. By using content analysis, this research has found that morals have several dichotomies. According to Alawi bin Abdul Qadir Ash-Saqâf in the Book of Mausû‘ah al-Akhlâq volume, the four moral dichotomies are divided into seven parts, including compassion, generosity, mutual glorification, generosity, hard work, positive thinking, and wisdom. Examples of application: 1) Love can take the form of tolerance, behavior, attitudes, words, actions. 2) An attitude of generosity is carried out by parents so that their children emulate these activities. 3) Respect each other by respecting the differences that exist in social life. 4) Generous, namely liking to help others, not being stingy when you have something, and liking to give. 5) Hard work, namely having a firm desire, never giving up, not giving up, and being confident in the success you will achieve. 6) Positive thinking, which results in a person having lots of ideas, having good prejudices, and having high self-confidence. 7) Wisdom, namely taking from a story, event and incident is called a lesson or advice.